2002
DOI: 10.1074/jbc.m201444200
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis-specific Activation of LIM Motif-containing Protein Kinase and Roles of Cofilin Phosphorylation and Dephosphorylation in Mitosis

Abstract: Actin filament dynamics play a critical role in mitosis and cytokinesis. LIM motif-containing protein kinase 1 (LIMK1) regulates actin reorganization by phosphorylating and inactivating cofilin, an actin-depolymerizing and -severing protein. To examine the role of LIMK1 and cofilin during the cell cycle, we measured cell cycleassociated changes in the kinase activity of LIMK1 and in the level of cofilin phosphorylation. Using synchronized HeLa cells, we found that LIMK1 became hyperphosphorylated and activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(151 citation statements)
references
References 41 publications
10
139
2
Order By: Relevance
“…As reported previously (Amano et al, 2002), phosphorylation of cofilin in control GFP cells increased in metaphase and then gradually decreased in telophase (Figure 4d). By contrast, LIMK2b links p53 to actin dynamics F-F Hsu et al phospho-cofilin in LIMK2b-GFP cells persisted in the later phase of cell division, which was very likely the result of heightened LIMK2 activity in these cells (Figure 4d).…”
Section: Overexpression Of Limk2b In Hela Cells Abrogates Cytokinesissupporting
confidence: 88%
See 1 more Smart Citation
“…As reported previously (Amano et al, 2002), phosphorylation of cofilin in control GFP cells increased in metaphase and then gradually decreased in telophase (Figure 4d). By contrast, LIMK2b links p53 to actin dynamics F-F Hsu et al phospho-cofilin in LIMK2b-GFP cells persisted in the later phase of cell division, which was very likely the result of heightened LIMK2 activity in these cells (Figure 4d).…”
Section: Overexpression Of Limk2b In Hela Cells Abrogates Cytokinesissupporting
confidence: 88%
“…This may not be totally unexpected because the ectopic expression of Xenopus LIMKs (Xlimk1/2) in oocytes inhibits meiotic progression (Takahashi et al, 2001). In addition, disruption of cofilin phosphorylation, which is normally transiently upregulated in the M-phase of the cell cycle (Amano et al, 2002), frequently results in failure of cytokinesis (Gunsalus et al, 1995;Abe et al, 1996;Hotulainen et al, 2005). These results suggest that proper modulation of cofilin phosphorylation is essential for successful cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that LIMK1 undergoes mitosis-specific activation by hyperphosphorylation, which is associated with a concomitant increase in phosphorylation of cofilin (29,32). LIMK1 becomes activated in prometaphase and metaphase and comes back to the basal level as cells enter telophase (32), which suggests that a controlled activity of cofilin by phosphorylation and dephosphorylation is necessary for mitosis. Our study indicates a direct role of LIMK1 in G 2 /M phase, as a partial reduction of LIMK1 expression induced a G 2 /M arrest in PC3ASL cells.…”
Section: Altered Expression Of Limk1 Changes Cell Morphology and Orgamentioning
confidence: 99%
“…4a), signifying a growth arrest in PC3ASL cells. A possible role of active LIMK1 in regulating mitosis has been suggested also, based on the studies that have shown that the LIMK1 activity fluctuates with cell cycle progression and attains a maximum level during mitosis when LIMK becomes hyperphosphorylated, presumably by mitotic Cdks (29,32). We used induced PC3ASL and PC3LacZ cells synchronized at G 1 /S boundary by double thymidine block and monitored cell cycle progression by harvesting cells at different time points after the release of the block.…”
Section: Limk1 Is Overexpressed In Cancerous Prostate Cells Andmentioning
confidence: 99%
“…To inhibit Aurora A, 100 nM MNL8237 was added with 10 M MG132 for 2 h before fixation. To measure Plk1 activity in mitosis, HeLa cells transfected with siRNAs were cultured in DMEM for 12 h and in thymidinecontaining medium for 36 h and then synchronized in early mitotic phase by 0.3 M nocodazole for 12-14 h. Mitotic cells were collected by the mechanical shake-off method (22). To prepare cells in which Plk1 is inactivated during mitosis, HeLa cells transfected with control siRNA were exposed to 300 nM BI-2536 for 2 h before collection.…”
Section: Methodsmentioning
confidence: 99%